In vitro and in silico Protective Effects of Ascorbic Acid on Nicotine-treated Human Erythrocytes (Preliminary Studies) - S Alamri, Ohoud Saeed; Faridi, Uzma (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: Nicotine is one of the most addictive naturally occurring drugs and is commonly found in tobacco products. Tobacco products are one of the most common causes of lung and oral cancer all over the world. As the main organ in contact with nicotine is the blood, our aim in the present study was to confirm its effect on the blood, We also studied the protective role of ascorbic acid on nicotine toxicity. Materials and Methods: Different blood toxicity study-related experiments such as Superoxide Dismutase (SOD), catalase, and total antioxidant capacity in erythrocytes were carried out using in vitro and in silico methods. Results and Conclusion: The results demonstrated that nicotine harms red blood cells in the lysis assay as well as the formation of clots in nicotine-treated samples in the blood clotting analysis. Also, the in silico method proved the validity of the in vitro results. Our research shows that ascorbic acid has protective effects on human blood. It was found that ascorbic acid increases SOD, catalase, and total antioxidant activity. Ascorbic acid also reduced the damage caused by nicotine to Red Blood Cells (RBCs) in the lysis assay, and it showed high protection from the formation of clots that formed when treating the samples with nicotine. The results indicate that the antioxidant ascorbic acid can protect against nicotine-induced hemological damage.
Keywords: Nicotine; in silico; in vitro; Ascorbic acid; Erythrocytes; Antioxidant